PENGARUH INVESTASI, TINGKAT PENDIDIKAN, UPAH MINIMUM KABUPATEN/KOTA, DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI BALI - Lestari, Leni; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Economic growth is one indicator of the economic progress of a country. The economic growth of the Province of Bali shows the occurrence of fluctuating disparities between regencies/cities, and even tends to decrease every year. The purpose of this study is to analyze the effect of investment, education level, UMK, and exports simultaneously and partially on the economic growth and analyze the variables that affect district/city economic growth in Bali Province. The data used is secondary data obtained from the Central Statistics Agency of Bali Province, with a total of 54 observations. The method of data collection in this study is the observation method. The analysis technique used is multiple linear regression analysis. The results showed that (1) investment, education level, UMK, and exports simultaneously had a significant effect on the economic growth of districts/cities in Bali Province, (2) investment, education level and exports partially had a positive and significant effect, while the UMK partially has a negative and significant effect on the economic growth of districts/cities in Bali Province, (3) the UMK are the variables that have the most dominant influence on the economic growth of districts/cities in Bali Province.